2017
DOI: 10.3390/ijms18030634
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides, Major Actors in Membrane Trafficking and Lipid Signaling Pathways

Abstract: Abstract:Phosphoinositides are lipids involved in the vesicular transport of proteins and lipids between the different compartments of eukaryotic cells. They act by recruiting and/or activating effector proteins and thus are involved in regulating various cellular functions, such as vesicular budding, membrane fusion and cytoskeleton dynamics. Although detected in small concentrations in membranes, their role is essential to cell function, since imbalance in their concentrations is a hallmark of many cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
160
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 136 publications
(184 reference statements)
4
160
0
3
Order By: Relevance
“…The PH‐Akt (GFP) probe is reactive to both PI (3,4)P2 and PI (3,4,5)P3 lipids (Manning & Cantley, ). These lipids have distinct biosynthetic and metabolic schemes (De Craene, Bertazzi, Bär, & Friant, ). To gain more insight into which of these phosphoinositides is displayed on LPVMs, we sought to determine whether the precursor lipids for PI (3,4)P2 and PI (3,4,5)P3 are also displayed on LPVs.…”
Section: Resultsmentioning
confidence: 99%
“…The PH‐Akt (GFP) probe is reactive to both PI (3,4)P2 and PI (3,4,5)P3 lipids (Manning & Cantley, ). These lipids have distinct biosynthetic and metabolic schemes (De Craene, Bertazzi, Bär, & Friant, ). To gain more insight into which of these phosphoinositides is displayed on LPVMs, we sought to determine whether the precursor lipids for PI (3,4)P2 and PI (3,4,5)P3 are also displayed on LPVs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, X-ray crystallography, coarse-grained MD, and reconstitution in artificial membranes have demonstrated that the Arf GTPase and its GEF Brag2 form a complex that binds to the membrane via multiple PI(4,5)P2 interaction sites (36). There is also mutational and biochemical evidence that profilin-1 and gelsolin have two PI(4,5)P2 binding sites, as do TRPV1 channels (45,62), EAG1 channels (17), and Kir2.1 (14,40).…”
Section: A Network Of Pi(45)p2 Binding Sitesmentioning
confidence: 99%
“…Intracellular trafficking events are modulated by several signaling molecules, which include members of the phosphoinositide family (35). In particular, the phosphatidylinositol (3,5)-bisphosphate [PI(3,5)P2] is critical for the trafficking along the endolysosomal system (68) and has been implicated in lysosome biogenesis and autophagy (912).…”
Section: Introductionmentioning
confidence: 99%